Evidence for a low-density Universe from the relative velocities of galaxies - Juszkiewicz, R; Ferreira, P; Feldman, H; Jaffe, A; Davis, M (2000)
The motions of galaxies can be used to constrain the cosmological density parameter Omega and the clustering amplitude of matter on large scales. The mean relative velocity of galaxy pairs, estimated from the Mark III survey, indicates that Omega = 0.35 +0.35/-0.25. If the clustering of galaxies is unbiased on large scales, Omega = 0.35 +/- 0.15, so that an unbiased Einstein-de Sitter model (Omega = 1) is inconsistent with the data.